Diversifikasi Produk Kopi Sidikalang: Pengembangan Scrub Berbasis Bahan Alami & Kearifan Lokal Untuk Mendorong Ekonomi Kreatif - Lesmita Munthe; Sanggam Pardede; Lasma Siagian (LPPM Universitas HKBP Nommensen, 2026)
This study aims to develop a preliminary design for a Sidikalang coffee-based scrub product and to formulate strategic steps to preserve and strengthen the local identity of the Sidikalang coffee-based scrub in order to support the growth of the creative economy. This study also analyzes the potential of Sidikalang coffee as an alternative ingredient for body care and formulates preservation strategies through product innovation. The method used is Research and Development (R&D) with the ADDIE model, which includes the Analysis, Design, Development, Implementation, and Evaluation stages. The analysis stage was conducted to identify the characteristics of the coffee and product development needs. The design stage covered the formulation, texture, and packaging design based on local identity. The development stage was carried out through prototype creation and expert validation. Implementation involved limited testing with users, while evaluation was conducted to assess the product’s feasibility and identify improvements. The research results indicate that Sidikalang coffee possesses characteristics suitable for use as a natural scrub ingredient and can be developed without compromising local cultural values. The product received a 97.76% rating from validators and elicited positive user feedback with an average feasibility score of 92.5%. Consequently, the Sidikalang coffee scrub product is deemed feasible and has the potential to support the preservation of local wisdom and the development of the region’s creative economy.